Outreach to Low-Wage and Precarious Workers: Concept Mapping for Public Health Officers. Issue 11 (November 2018) - Velonis, Alisa; Forst, Linda
Abstract : Objective: To explore concept mapping (CM) as a participatory methodology that can be used by public health officials to strategize approaches to reducing health inequities among low wage workers and workers with unstable employment. Methods: In a workshop of 68 occupational health officers, mainly from government agencies, CM was demonstrated through gathering and prioritizing ideas for reaching underserved, at-risk working populations. Results: Prior to the workshop, occupational health officers generated 99 brainstormed ideas on how to reach underserved workers. These were reduced to 39 unique items, which workshop participants then sorted into themes and prioritized based on perceived effectiveness and feasibility. Twelve specific approaches covering enhanced surveillance methods, occupational safety and health (OSH) training, and partnering with employers, other agencies, and community groups were considered most actionable by occupational/public health officers to address the health of low-wage, and precarious workers. In a follow-up session 1 year later, a subset of participants discussed the findings. Conclusion: Concept mapping can be used to elucidate actionable approaches by government agencies to better address occupational health inequities experienced by low wage and precarious workers.